Evaluation of polyoxymethylene dimethyl ethers as a new type of diesel additives. (15th December 2018) - Qi, Jianguang; Hu, Yufeng; Niu, Jiangge; Ma, Weiting; Jiang, Siqi; Wang, Yichuang; Zhang, Xianming; Jiang, Yuehui
Highlights: Adding PODE n increases density, abrasion resistance and cold filter plugging point. Addition of PODE n decreases viscosity and flash point. (Diesel + PODE n ) may exhibit minimum flash point behavior. Effects of PODE n on cetane number, solidifying point, heat capacity rely on diesel. Newly developed equations accurately predict density, viscosity and heat capacity. Abstract: Polyoxymethylene dimethyl ethers (PODE n ) is an emerging biofuel that has a great potential to become one of the competitive alternative fuels for diesel engine. In the present study, systematic studies were made to evaluate the influences of PODE n on the physical fuel properties that are routinely used to define the quality of diesel fuels. Such fuel properties were measured for the three (diesel + PODE n ) mixtures, diesels, and PODE n . The measured properties included cetane number, lubricity, density, viscosity, solidifying point, cold filter plugging point, flash point, and heat capacity. Comparisons of measured properties of the mixtures and their individual components were made to achieve the following purposes: First, to reveal the changes in the properties of diesels upon the addition of PODE n and in the properties of the (diesel + PODE n ) mixtures as the weight percent of PODE n is increased; Second, to see whether or not the addition of PODE n worsens the properties of diesels, in particular, whether or not the measured values of the (diesel + PODE n ) mixtures exceed the standard values set by the Beijing-VI. Novel theoretical equations were developed to quantitatively predict the density, viscosity, and heat capacity of the (diesel + PODE n ) mixtures in terms of the corresponding properties of the diesel and PODE n . Comparisons were made between measured and predicted properties and the agreements are excellent.